2021
DOI: 10.1038/s41467-021-24715-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the molecular bushing of the bacterial flagellar motor

Abstract: The basal body of the bacterial flagellum is a rotary motor that consists of several rings (C, MS and LP) and a rod. The LP ring acts as a bushing supporting the distal rod for its rapid and stable rotation without much friction. Here, we use electron cryomicroscopy to describe the LP ring structure around the rod, at 3.5 Å resolution, from Salmonella Typhimurium. The structure shows 26-fold rotational symmetry and intricate intersubunit interactions of each subunit with up to six partners, which explains the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Replacing this with a positively charged lysine residue would alter the electrostatic potential in this area, potentially interfering with phage assembly. It is therefore likely that a mixture of both attractive and repulsive forces are important for phage assembly and egress, similar to the findings reported for the assembly and rotation of the bacterial flagellar rod 49 .…”
Section: Discussionsupporting
confidence: 80%
“…Replacing this with a positively charged lysine residue would alter the electrostatic potential in this area, potentially interfering with phage assembly. It is therefore likely that a mixture of both attractive and repulsive forces are important for phage assembly and egress, similar to the findings reported for the assembly and rotation of the bacterial flagellar rod 49 .…”
Section: Discussionsupporting
confidence: 80%
“…Recently, Johnson et al (2021), Yamaguchi et al (2021), and Tan et al (2021) reported the molecular structures of the flagellar P‐ and L‐rings from S. enterica . Johnson and colleagues observed an outer ring formed by a protein called YecR surrounding the L‐ring in their structure, which they hypothesized helps to remodel the lipid bilayer around the L‐ring protein, thereby facilitating its assembly in the OM.…”
Section: Discussionmentioning
confidence: 99%
“…Like GldK/PorK, FlgH is a lipoprotein and like GldN/PorN, FlgI is a periplasmic protein. The LP ring of the flagellar motor interacts with the distal end of the driveshaft (rod), supports stable rotation of the rod, and reduces friction ( Yamaguchi et al, 2021 ). The GldK/PorK-N ring may play a similar role in T9SS rotation.…”
Section: The Mechanism Of Rotation and Comparison Of Type 9 Secretion...mentioning
confidence: 99%